Human sLZIP promotes atherosclerosis via MMP‐9 transcription and vascular smooth muscle cell migration. Issue 11 (30th July 2014) - Kim, Jeonghan; Ko, Jesang
Abstract : Atherosclerosis is a chronic inflammatory response of the vascular wall, and immune responses are involved in every phase of atherosclerosis, from initiation, to progression, and finally to plaque rupture. Cytokines are the major atherogenic mediators that promote plaque formation and progression by activation of inflammatory cells. They induce expressions of matrix metalloproteinases (MMPs), leading to vascular smooth muscle cell (VSMC) migration in atherosclerotic lesions. Although chronic inflammatory mediators, including tumor necrosis factor α (TNF‐α) and MMPs, exacerbate atherosclerosis, the molecular mechanism of atherogenesis remains unclear. In this study we investigated the role of a novel transcription factor the human small leucine zipper protein (sLZIP) in TNF‐α‐induced MMP expression, VSMC migration, and atherosclerosis progression. The proinflammatory cytokine TNF‐α enhanced sLZIP expression by 3‐fold via activation of NF‐κB signaling. sLZIP induced MMP‐9 transcription and the proteolytic activity of MMP‐9 by 2.8‐ and 3.2‐fold ( P < 0.05), respectively, in macrophages, leading to enhancement of VSMC migration by 2.7‐fold ( P <0.005). sLZIP OE/+ (sLZIP transgenic); LDLR ‐/‐ mice fed a high‐cholesterol diet exhibited enhanced arterial plaque formation and increased VSMC migration from the media into the intima by 2.8‐ and 2.6‐fold ( P <0.01), respectively, compared with atherosclerosis‐prone LDLR ‐/‐ mice. These results indicate that human sLZIP plays a critical role in development of atherosclerosis and can be used as a therapeutic target molecule for treatment of atherosclerosis.—Kim, J., Ko, J., Human sLZIP promotes atherosclerosis via MMP‐9 transcription and vascular smooth muscle cell migration. FASEB J. 28, 5010–5021 (2014). www.fasebj.org